Religious and political consolidation in Southern Dagestan in 2010-2020: the inclusion of local communities in the general Dagestan Muslim space - M. M. Gadzhiev (Современная наука и инновации, 2024)
This article analyzes a little-studied aspect of the consolidation of Dagestan society in 2010-2020: how the process of religious and political unification took place in Southern Dagestan. The paper traces the process of alternation of political and administrative-coercive methods in the unification of local Islamic communities in the region. The author proves that the murder of Sheikh Sirazhudin Khuriksky, who had maintained the religious independence of Southern Dagestan since the 1990s, was a turning point in the process of eliminating the religious autonomy of this sub-region. These changes coincided with the coming to the post of the head of Dagestan Ramazan Abdulatipov, who actively interfered in local politics. The Dagestan Muftiate took advantage of this situation to extend its influence to Southern Dagestan. The described processes led to the consolidation of political power in the republic and the unification of the Muslim space. The former fragmentation and complication of religious and political life have been stopped. Because they threatened the emergence of uncontrolled processes associated with the radicalization of Dagestan Muslim society.